An in vitro 3D model using collagen coated gelatin nanofibers for studying breast cancer metastasis. (7th February 2017) - Janani, G; Pillai, Mamatha M; Selvakumar, R; Bhattacharyya, Amitava; Sabarinath, C
Abstract: The study of breast cancer metastasis is limited due to poor knowledge of molecular progression of breast tumor and varied heterogeneity. For a better understanding of tumor metastasis, a reliable 3D in vitro model bridging the gap between 2D cultures and in vivo animal model studies is essential. Our study is focused on two key points: (i) designing a 3D microenvironment for studying metastasis and (ii) simulating the metastasis milieu by inducing epithelial to mesenchymal transition (EMT) and mesenchymal to epithelial transition (MET). An electrospun gelatin nanofiber matrix (EGNF) was fabricated using electrospinning and further dip coated with different concentrations of collagen to obtain surface complexity and mechanical properties, similar to connective tissues. Nanofiber matrices were physically characterized by Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), and field-emission scanning electron microscopy (FESEM). The FTIR, AFM, and FESEM results indicated the crosslinking and confirmed the presence of pores in the nanofiber matrices. Comparative studies on biocompatibility, cell attachment, and the proliferation of MCF-7 cells on EGNF and collagen coated gelatin nanofibrous matrix (CCGM) revealed higher cellular attachment and proliferation in CCGM. CCGM with human metastatic breast cancer cell line (MCF-7) was taken to study breast cancer metastasis using estrogen (induces EMT) and progesterone (induces MET) hormones for 24 h. Quantitative real-time PCR was used for quantifying the expression of metastasis related genes, and fluorescence microscopy for verifying the invasion of cells to the matrices. The expression of E-cadherin and matrix metalloproteinase 2 (MMP 2) confirmed the occurrence of EMT and MET. Live cell imaging and cellular attachment showed significant increase of cellular invasion in crosslinked 0.15% CCGM that serves as a suitable non-toxic, biocompatible, and affordable scaffold for studying breast cancer metastasis. Our findings suggested that CCGM can be used as a tissue-like 3D model for studying breast cancer metastatic events in vitro .